Mitochondria damaged by Oxygen Glucose Deprivation can be Restored through Activation of the PI3K/Akt Pathway and Inhibition of Calcium Influx by Amlodipine Camsylate - Park, Hyun-Hee (Sci Rep, 2019)
Amlodipine, a L-type calcium channel blocker, has been reported to have a neuroprotective effect in brain ischemia. Mitochondrial calcium overload leads to apoptosis of cells in neurologic diseases. We evaluated the neuroprotective effects of amlodipine camsylate (AC) on neural stem cells (NSCs) injured by oxygen glucose deprivation (OGD) with a focus on mitochondrial structure and function. NSCs were isolated from rodent embryonic brains. Effects of AC on cell viability, proliferation, level of free radicals, and expression of intracellular signaling proteins were assessed in OGD-injured NSCs. We also investigated the effect of AC on mitochondrial structure in NSCs under OGD by transmission electron microscopy. AC increased the viability and proliferation of NSCs. This beneficial effect of AC was achieved by strong protection of mitochondria. AC markedly enhanced the expression of mitochondrial biogenesis-related proteins and mitochondrial anti-apoptosis proteins. Together, our results indicate that AC protects OGD-injured NSCs by protecting mitochondrial structure and function. The results of the present study provide insight into the mechanisms underlying the protective effects of AC on NSCs.